Electrolyzed water: a promising strategy for improving food quality and safety of fruits, vegetables, and meat - Meghwar, Parkash; Saeed, Syed Muhammad Ghufran; Forte, Lucrezia; Smaoui, Slim; Khalid, Nurul Izzah; De Palo, Pasquale; Maggiolino, Aristide (Wiley, 2024)
The growing demand for sustainable and healthy practices has led to an increased interest in the electrolyzed water (EW)application. Tis technology has garnered widespread acceptance as a sanitizer within the food industry. It also enhances the nutritional, functional, and sensory properties of food products to improve quality and safety. Tis review undertakes a comprehensive review of the recent advancements in electrolysis technology, exploring its applications in fruits and meat industry and its impact on nutritional, functional, microbiological, safety, and sensory characteristics. It is concluded that the EW should be considered an essential component of industrial equipment sanitization and food product decontamination by offering anti-microbial benefits and promoting functional component accumulation. Nevertheless, the effectiveness of EW can be com-promised by the presence of organic matter and equipment corrosion. Furthermore, it provides a concise overview of EW generation, elucidates the influential factors governing its production, and delineates prospective directions for research and development in this field.